Influence of different amounts of milk replacer on esophageal leakage, rumen fermentation characteristics, gastrointestinal tract passage rate, and microbial crude protein synthesis of nursling animals - Jardeson de Souza Pinheiro; Paulo Sergio Dornelas Silva; Dhones Rodrigues de Andrade; Erollykens Ferreira Santos; Adailton Camêlo Costa; Nathalia Veloso Trópia; Sebastião de Campos Valadares Filho; Edenio Detmann; Simone Eliza Facione Guimarães; Marcos Inacio Marcondes (Journal of Dairy Science)
ABSTRACT: We aimed to evaluate the esophageal leakage, ruminal fermentation characteristics, passage rate, and microbial crude protein (MCP) synthesis and its flow in the immature rumen of preweaning animals fed different amounts of liquid diet. Sixty newborn male kids, not castrated, from Saanen and Swiss Alpine breeds, with BW of 3.834 ± 0.61 kg (mean ± SD), were distributed in a randomized block design in a 2 × 6 factorial scheme composed of 2 nutritional plans (either 1 L or 2 L of milk replacer [MR] per kid per day), and 6 time points of slaughter after feeding. Breeds were the blocking factor in the model (random effect). All kids were slaughtered at 45 d of life. Esophageal leakage was not affected by the nutritional plan. Esophageal leakage into the rumen averaged 56.0%, whereas 42.0% leaked directly into the abomasum. Furthermore, a low proportion (2.0%) of the MR escaped immediately into the small intestine. Passage rates were also not affected by the nutritional plan (P > 0.050). Milk replacer passage rates were 0.290 h−1, 0.307 h−1, and 0.369 h−1, and their respective mean retention times were 3.44 h, 3.22 h, and 6.06 h in the kids' rumen, abomasum, and small intestine, respectively. Microbial crude protein synthesis was not affected by the nutritional plan, averaging 1.95 (g/day) for the kids. Lastly, most ruminal fermentation characteristics were affected by the nutritional plans and slaughter time after feeding, such as ammonia, soluble protein, and VFA. In conclusion, a high MR allowance influences performance and rumen parameters without affecting esophageal leakage, passage rates, and MCP synthesis in preweaning dairy kids.